2000
DOI: 10.15760/etd.2338
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership, Diversity, and Creativity at Work: A Moderated Mediation Model

Abstract: Organizational leaders often seek to hire and retain innovative employees as a source of competitive advantage. Both transformational leadership and effectively managed workplace diversity have been theorized and shown to lead to increased employee creative performance at work; however, a full model of the relationships between leadership and the multi-dimensional construct of workplace diversity has not yet been tested. Using a sample of 371 employees in three Chinese high-technology firms matched with 64 sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 254 publications
(127 reference statements)
3
6
0
Order By: Relevance
“…This result translates to a situation where shared perceptions regarding diversity policies and practices will constructively assist employees in demonstrating commitment towards the organisation when they are exposed to the characteristics of transformational leadership in their specific workplaces. Thus, the mediation result for the path of transformational leadership to organisational commitment via diversity confirms the mediating promises of a diversity climate as demonstrated by Volpone et al (2012) and Taylor (2015).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This result translates to a situation where shared perceptions regarding diversity policies and practices will constructively assist employees in demonstrating commitment towards the organisation when they are exposed to the characteristics of transformational leadership in their specific workplaces. Thus, the mediation result for the path of transformational leadership to organisational commitment via diversity confirms the mediating promises of a diversity climate as demonstrated by Volpone et al (2012) and Taylor (2015).…”
Section: Discussionsupporting
confidence: 70%
“…We could also not find a similar South African study that has investigated diversity climate as mediating transformational leadership. However, from previous research conducted by Volpone, Avery and McKay (2012), Chrobot-Mason and Asomovich (2013) and Taylor (2015), we were able to find evidence that an organisational diversity climate demonstrates promising mediating characteristics. Volpone et al (2012) demonstrated that diversity climate mediates the relationship between employees' appraisal reactions and employee engagement.…”
Section: Proposed Mediation Model: Diversity Climatementioning
confidence: 49%
See 1 more Smart Citation
“…In their study on ethical preferences of transformational leaders, Priyanka Banerji & Venkat R. Krishnan (2000), and other scholars, recounted that transformational leadership includes inspiring, mustering, uplifting, and raising the moral objectives of the leader and of the led (Banerji & Krishnan, 2000;Lee, 2014;and Taylor, 2015). Going by the meta-analysis findings of studies in transformational leadership literature, K.B.…”
Section: Resultsmentioning
confidence: 99%
“…The word creativity is derived from the Latin word "Creatus" or "Creare", intends to make. The most normally acknowledged meaning of creativity in the U.S. is the creation of novel and valuable thoughts concerning items, administrations, procedures, and methodology that are acknowledged inside significant areas (Taylor, 2015). Creativity refers to the creative ability to begin or make new considerations, ideas, and thoughts (Asghar & Sultana, 2017).…”
Section: Literature Review Employee Creativitymentioning
confidence: 99%